Locating neighbourhood diversity in the American metropolis. (January 2018) - Walker, Kyle
Racial and ethnic diversity in the United States is on the rise, as the country is projected to no longer have a racial majority by the mid-2040s. Much of this diversity is found in the United States' large metropolitan areas, where it manifests itself unevenly. While some metropolitan neighbourhoods are growing highly diverse, others remain segregated by race and ethnicity. This paper introduces a framework for exploring the geography of neighbourhood diversity in US metropolitan areas, and defines the diversity gradient, a visual representation of how diversity varies with distance from the urban core. Analysis of the geography of metropolitan diversity from 1990 to 2010 reveals that the greatest increases in diversity are found in the suburbs and outlying areas, where diversity now peaks in many large metropolitan areas. Additional spatial analyses of neighbourhood diversity in Chicago and Dallas-Fort Worth show that clustering of highly diverse neighbourhoods has shifted to the suburbs from close-in urban areas, where many segregated and low-diversity neighbourhoods persist.